Social Anxiety in Early Adulthood in Developing Social Interactions on Campus: A Case Study of the Islamic Guidance and Counseling Study Program - Fathir Rizky; Ira Wirtati (Scidacplus, 2026)
This study aims to analyze the forms of social anxiety, the factors that influence it, and its impact on students' ability to build interpersonal relationships in the Islamic Guidance and Counseling Study Program at the State Islamic University of North Sumatra. The study uses a qualitative approach with a case study design. Participants consisted of eight students aged 19–23 who were selected using purposive sampling. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using thematic analysis with triangulation techniques to ensure data validity. The results show that social anxiety is manifested in the form of physiological symptoms (heart racing, sweaty hands, and tense body), cognitive and behavioral symptoms such as fear of negative evaluation, overthinking, low self-confidence, and a tendency to avoid social interactions. Social anxiety is influenced by internal factors, including an introverted personality, insecurity, and low self-efficacy, as well as external factors like adapting to campus life, negative social experiences, and cultural or language barriers. Its impact is seen in students' difficulties in starting interactions, participating in academic activities, and building interpersonal relationships, although most are able to adapt as social support and positive experiences on campus increase. The novelty of this study lies in revealing the contextual form of social anxiety, including cross-cultural communication barriers and anxiety in interactions based on perceived social status, and emphasizing that social anxiety affects the quantity of interactions more than the quality of interpersonal relationships that are successfully built. These findings have implications for developing counseling and guidance services at universities that focus on improving students' communication skills, peer support, and social adaptability.